2015
DOI: 10.1016/j.fsi.2015.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Advances in gastropod immunity from the study of the interaction between the snail Biomphalaria glabrata and its parasites: A review of research progress over the last decade

Abstract: This review summarizes the research progress made over the past decade in the field of gastropod immunity resulting from investigations of the interaction between the snail Biomphalaria glabrata and its trematode parasites. A combination of integrated approaches, including cellular, genetic and comparative molecular and proteomic approaches have revealed novel molecular components involved in mediating Biomphalaria immune responses that provide insights into the nature of host-parasite compatibility and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 121 publications
0
74
0
Order By: Relevance
“…This recognition pattern may be associated with the specificity of the mollusc-helminth interactions (PEREIRA et al, 2008). It should also be noted that the mollusc innate immune system, comprised of haemocytes and hemolymph soluble factors can recognize not only the parasite and excreted-secreted products (ES), but also the induced inflammation process (COUSTAU et al, 2015) a fact not demonstrated in this study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This recognition pattern may be associated with the specificity of the mollusc-helminth interactions (PEREIRA et al, 2008). It should also be noted that the mollusc innate immune system, comprised of haemocytes and hemolymph soluble factors can recognize not only the parasite and excreted-secreted products (ES), but also the induced inflammation process (COUSTAU et al, 2015) a fact not demonstrated in this study.…”
Section: Discussionmentioning
confidence: 68%
“…Despite the high specificity between molluscs and trematodes, immunobiological studies between F. hepatica and lymnaeids are little explored. Nevertheless, the recognition of the trematode by the mollusc's internal defense system, made by haemocytes and soluble factors present in the haemolymph, from the penetration of miracidium to the transformation of sporocyst followed by the formation of rediae until the release of cercariae, may resemble the associations reported for other digenetic trematodes and gastropod molluscs (PEREIRA et al, 2008;CARON et al, 2014;COUSTAU et al, 2015). Fluctuations in the number of Lymnaea stagnalis haemocytes in the haemolymph during infection by Trichobilharzia ocellata have been observed ( VAN DER KNAAP et al, 1987;AMEN et al, 1991).…”
Section: Introductionmentioning
confidence: 75%
“…The immune system of Biomphalaria is composed of cellular and humoral components acting independently or together to fight invading microbes or parasites [51,52]. The first line of defense is mediated by circulating phagocytic cells known as hemocytes (also known as amoebocytes) found in the hemolymph of the snail.…”
Section: Discussionmentioning
confidence: 99%
“…Erwin et al, 2011). As such, study of molluscs will continue to broaden understanding of the evolution of immune function across the range of metazoan phylogeny, especially because recent insights suggest that molluscs are capable of sophisticated and specific immune responses (Adema and Loker, 2015; Coustau et al, 2015; Guo et al, 2015). …”
Section: Introductionmentioning
confidence: 99%